ʺTraining future teachers to organize educational activities using information and communication technologiesʺ - Pavlova, O. (Problems of Engineer-Pedagogical Education, 2024)
The article focuses on the current stage of societal development characterized by the informatization of the vast majority of life spheres. An integral part of this process is the use of information and communication technologies in education, particularly in the upbringing process, where these technologies are expected to enhance efficiency. Consequently, modern educators need to skillfully utilize information and communication technologies in their professional activities. The potential of using these technologies in organizing the educational process in secondary education institutions is justified. The development and utilization of information and communication technologies in the educational process aim to change traditional forms of upbringing organization and offer significant advantages in the information society and in response to contemporary challenges. A crucial quality of modern information and communication technologies is their universality, as they can serve as the foundation for organizing any activity related to information exchange, creating a common information space, and more. The application of ICT contributes to improving all types of educational work. The article also addresses aspects of the professional training of future educators in organizing educational activities using information and communication technologies. An analysis of the scientific literature indicates that a high level of ICT competence is a crucial condition for the effectiveness of a teacher's professional activities. The specificity of studying information and communication technologies, including their use as a means of upbringing in higher education pedagogical institutions, is identified. Emphasis is placed on the fact that direct formation of ICT skills in future professional activities significantly enhances the intensity and effectiveness of training for future teachers. Moreover, the main goals of preparing future primary school teachers to organize educational activities using information and communication technologies are outlined.